Utilization and Effectiveness of Home Treatment for People With Acute Severe Mental Illness: A Propensity-Score Matching Analysis of 19 Months of Observation - Mötteli, Sonja; Schori, Dominik; Schmidt, Helen; Seifritz, Erich; Jäger, Matthias (Frontiers in Psychiatry, 2018)
Treatment guidelines recommend home treatment (HT) as an effective alternative to inpatient treatment for individuals with severe, acute mental illness (SAMI). Nevertheless, HT is largely unfamiliar in German-speaking countries. Here we examined the utilization and effectiveness of HT services newly implemented in a large hospital setting in Switzerland. We used a naturalistic observational study design including patients (n = 201, 18–65 years, 65.7% females) with SAMI who received HT between June 2016 and December 2017. HT patients were compared with a crude inpatient sample (n = 1078) and a matched inpatient sample (n = 201). Propensity-score matching was used to control for personal characteristics. Treatment outcomes were compared between HT patients and the matched inpatients based on routinely obtained medical data. The results showed that the HT sample consisted of more females (+21%), older (+4 years), and better educated (+10%) patients with more affective disorders (+13%) and less substance use disorders (−15%) as compared with the crude inpatient sample. The severity of symptoms was the same. After matching, there were no significant differences in the proportion of readmissions (36%), the duration until readmission and scores of the Health of the Nation Outcome Scales (HoNOS). The treatment duration of HT patients was significantly longer and, post-treatment, scores on the Global Assessment of Functioning scale (GAF) were significantly better. We conclude that HT is an effective treatment option for patients with SAMI also in Switzerland concerning the reduction of hospital days, the improvement of symptoms and functioning and readmission rates. HT cannot fully replace hospital admissions in all cases and HT may be beneficial for particular groups of patients (e.g., females and individuals with affective disorders). The study further shows the potential value of propensity-score matching in health care service research.